The Gap to Fill: Rationale for Rapid Initiation and Optimal Titration of Comprehensive Disease-modifying Medical Therapy for Heart Failure with Reduced Ejection Fraction - Nicholas K Brownell (Radcliffe Medical Media, 2021)
There are gaps in the use of therapies that save lives and improve quality of life for patients with heart failure with reduced ejection fraction, both in the US and abroad. The evidence is clear that initiation and titration of guideline-directed medical therapy (GDMT) and comprehensive disease-modifying medical therapy (CDMMT) to maximally tolerated doses improves patient-focused outcomes, yet observational data suggest this does not happen. The purpose of this review is to describe the gap in the use of optimal treatment worldwide and discuss the benefits of newer heart failure therapies including angiotensin receptor-neprilysin inhibitors and sodium-glucose cotransporter 2 inhibitors. It will also cover the efficacy and safety of such treatments and provide potential pathways for the initiation and rapid titration of GDMT/CDMMT.